RUSSIAN HISTORIOGRAPHY OF THE 1970-S – EARLY XXI CENTURY ON THE IDEOLOGICAL AND POLITICAL LIFE OF RUSSIA IN 1971 – 1991 - M. V. Kazmina; V. N. Kazmin (Вестник Кемеровского государственного университета, 2017)
The article considers the main stages of the historiography of the ideological and political life of Russia in 1971 – 1991, the authors distinguish two stages of the  historiography  problems:  1971  –  late  1980s  -  the  beginning  of  1990s; end 1980s - the beginning of 1990s - beginning of XXI century. The first stage is characterized by methodological monism. The main attention of researchers was paid to the problems of propaganda of Marxist-Leninist ideology, ideological and political education of Soviet citizens. The second phase of historiography was methodological revolution when there a critical re-evaluation of the historical way the Soviet State had passed took place. The main focus of historical research during Perestroika was on such problems as: dissidence, protest movement, the activities of informal organizations. The article analyzes the historiography of dissidence and concludes that researchers created a scientific base that can serve as a basis for further study of this topic.